The Regulation of Systemically Relevant Banks How Governments Should Manage Their Exposure to Banking System Risk - Moenninghoff, Sebastian C. (Finanzwirtschaft, Banken und Bankmanagement I Finance, Banks and Bank Management,, 2018)
Sebastian Moenninghoff provides an extensive overview of the status of the 'Too-Big-to-Fail' doctrine post-crisis and develops the first comprehensive framework to categorize and discuss the full range of major policy options for regulating banks. Governments need to actively manage their exposure to banking system risk with the optimal policy mix depending on risk return preferences of a society and an economy's institutional setting. The new regulation for global systemically important banks developed by international regulators following the financial crisis is a significant step in expanding the tools to manage government exposure to banking system risk. Contents Comprehensive Review of the Post-Crisis Status of the 'Too-Big-to-Fail' Doctrine Novel Quantitative Framework to Categorize and Discuss the Full Range of Major Policy Options for Bank Regulation Empirical Examination of the New International Regulation Dealing with Global Systemically Important Banks Target Groups Researchers and students in the fields of economics with a focus on finance and banking Practitioners in the fields of financial services, banking, regulation, politics, and journalism The Author Sebastian Moenninghoff works in the financial services industry in New York. He has extensive experience advising financial institutions in the U.S. and Europe during and after the financial crisis and has published and taught on banking regulation and financial innovation.